2000
DOI: 10.1111/j.1749-6632.2000.tb06193.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Antioxidants from Marijuanaa

Abstract: A BSTRACT : Cannabidiol and other cannabinoids were examined as neuroprotectants in rat cortical neuron cultures exposed to toxic levels of the neurotransmitter, glutamate. The psychotropic cannabinoid receptor agonist ⌬ 9tetrahydrocannabinol (THC) and cannabidiol, (a non-psychoactive constituent of marijuana), both reduced NMDA, AMPA and kainate receptor mediated neurotoxicities. Neuroprotection was not affected by cannabinoid receptor antagonist, indicating a (cannabinoid) receptor-independent mechanism of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(121 citation statements)
references
References 14 publications
3
117
1
Order By: Relevance
“…CBD reduces oxidative toxicity in an in vitro glutamate excitotoxicity assay [123], and raises adenosine to oppose lipopolysaccharideinduced inflammation and tumor necrosis factor-α release [118,124]. In mice with middle cerebral artery occlusion, CBD triggered a CB 1 R-independent decrease in reperfusion injury, inflammation, and death.…”
Section: Cbdmentioning
confidence: 95%
“…CBD reduces oxidative toxicity in an in vitro glutamate excitotoxicity assay [123], and raises adenosine to oppose lipopolysaccharideinduced inflammation and tumor necrosis factor-α release [118,124]. In mice with middle cerebral artery occlusion, CBD triggered a CB 1 R-independent decrease in reperfusion injury, inflammation, and death.…”
Section: Cbdmentioning
confidence: 95%
“…More specifically, it has been suggested that cannabis attenuates the neurotoxic effects of ecstasy, as cannabis and ecstasy may have opposite effects on oxidative stress . Ecstasy is thought to cause increased oxidative stress, thereby enhancing the risk for serotonergic neurotoxicity (Green et al 2003), whereas cannabis may act as an antioxidant (Hampson et al 2000), and therefore, possibly has neuroprotective effects (Sinor et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanisms of the neuroprotective effect of cannabinoids are not completely understood, cannabinoids have been suggested to be involved in numerous processes, such as the modulation of calcium homeostasis and excitability [111,112] , regulation of immune and inflammatory responses [113,114] , activation of cytoprotective signalling pathways [112] , as well as modulations of synaptic plasticity, excitatory glutamatergic transmissions [111] and their hypothermic and antioxidant properties [115] . In this regard, the endocannabinoid system may also represent a pivotal neuroprotective mechanism both in chronic neurodegenerative disorders and in acute forms of neuronal injury.…”
Section: Therapeutic Potential Of Cannabinoid After Hypoxia-ischemiamentioning
confidence: 99%